Temozolomide-induced hypermutation is associated with distant recurrence and reduced survival after high-grade transformation of low-grade IDH-mutant gliomas. Issue 11 (5th April 2021) - Yu, Yao; Villanueva-Meyer, Javier; Grimmer, Matthew R; Hilz, Stephanie; Solomon, David A; Choi, Serah; Wahl, Michael; Mazor, Tali; Hong, Chibo; Shai, Anny; Phillips, Joanna J; Wainer, Bruce H; et al.
Abstract: Background: Chemotherapy improves overall survival after surgery and radiotherapy for newly diagnosed high-risk IDH -mutant low-grade gliomas (LGGs), but a proportion of patients treated with temozolomide (TMZ) will develop recurrent tumors with TMZ-induced hypermutation. We aimed to determine the prevalence of TMZ-induced hypermutation at recurrence and prognostic implications. Methods: We sequenced recurrent tumors from 82 patients with initially low-grade IDH -mutant gliomas who underwent reoperation and correlated hypermutation status with grade at recurrence and subsequent clinical outcomes. Results: Hypermutation was associated with high-grade disease at the time of reoperation (OR 12.0 95% CI 2.5-115.5, P = .002) and was identified at transformation in 57% of recurrent LGGs previously exposed to TMZ. After anaplastic (grade III) transformation, hypermutation was associated with shorter survival on univariate and multivariate analysis (HR 3.4, 95% CI 1.2-9.9, P = .024), controlling for tumor grade, subtype, age, and prior radiotherapy. The effect of hypermutation on survival after transformation was validated in an independent, published dataset. Hypermutated (HM) tumors were more likely to develop discontiguous foci of disease in the brain and spine ( P = .003). To estimate the overall incidence of high-grade transformation among low-grade IDH -mutant tumors, data from a phase II trial of TMZ for LGG were analyzed. Eight-year transformation-free survival was 53.8% (95% CI 42.8-69.2), and 61% of analyzed transformed cases were HM. Conclusions: TMZ-induced hypermutation is a common event in transformed LGG previously treated with TMZ and is associated with worse prognosis and development of discontiguous disease after recurrence. These findings impact tumor classification at recurrence, prognostication, and clinical trial design.